Bio-electrochemical impedance spectroscopy and X-ray computed tomography analysis of prefreezing-induced cell-structure changes in sweet potatoes and their impacts on the physical properties after baking. (January 2022) - Lee, Younju; Watanabe, Takashi
Abstract: The cell structure of fruits and vegetables is changed due to freezing. The application of these changes by prefreezing for improving the physical quality of baked sweet potatoes was investigated here. The cell structures and physical properties were analyzed focusing on bio-electrochemical impedance spectroscopy (BIS), X-ray computed tomography (X-ray CT), increasing sample temperature, and mechanical properties. The BIS indicated that the cell membranes were destroyed by both freezing and baking. The X-ray CT images showed that the frozen-baked sample could be maintained more inside the tissue area than the raw-baked sample: this indicated that prefreezing significantly inhibited shrinkage during baking. Moreover, the freezing treatments significantly reduced the temperature increase during baking, maximum penetration stress, and elastic modulus of their tissues, which could be attributed to ice crystallization. This study suggests that prefreezing may be effective for the storage, control, or improvement in physical quality of baked sweet potatoes. Graphical Abstract: ga1 Highlights: Effect of pre-freezing treatment on physical qualities of baked sweet potatoes. Cell structure changes are assessed by bio-electrochemical impedance and X-ray CT. Pre-freezing affects the shrinkage, temperature increase, hardening during baking. The relationships between the cell structure and physical properties changes.